(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess nurses’ knowledge and attitudes regarding pain management and to identify associated factors at Nghe An Oncology Hospital in 2025. Methods: A cross-sectional descriptive study was conducted from February to September 2025 among 310 nurses providing direct patient care at clinical departments of Nghe An Oncology Hospital. Eligible participants were recruited using total population sampling. Data were collected using a self-administered questionnaire including demographic characteristics and the Nurses’ Knowledge and Attitudes Survey Regarding Pain (NKASRP). Statistical analyses were performed using SPSS version 22.0. Descriptive statistics and association analyses were conducted, with statistical significance set at p < 0.05. Results: The mean knowledge score was 8.8 ± 3.31, while the mean attitude score was 63.04 ± 6.45. Only 5.5% of nurses achieved a high level of knowledge, whereas 47.7% and 46.8% demonstrated moderate and low knowledge levels, respectively. Regarding attitudes, 0.6% of nurses showed positive attitudes, 92.0% had moderate attitudes, and 7.4% had poor attitudes. Knowledge was significantly associated with attitude (p = 0.003). Educational level and years of professional experience were significantly associated with nurses’ knowledge and attitudes toward pain management (p < 0.05). No statistically significant associations were found between knowledge or attitudes and gender, personal pain experience, or previous pain management training. Conclusion: Nurses at Nghe An Oncology Hospital demonstrated insufficient knowledge and suboptimal attitudes regarding pain management. Educational attainment and professional experience were identified as significant associated factors. Continuous education programs and standardized evidence-based pain management protocols are recommended to improve nursing practice and enhance the quality of patient care.